Comparative study of net energy metering and feed-in tariff for the 496kWp UiTM segamat solar photovoltaic system - Muhamad Firdaus Zambri; Muhammad Murtadha Othman; Kamrul Hasan; Muhamad Nabil Hidayat; Abdul Kadir Ismail; Ismail Musirin (Institute of Advanced Engineering and Science, 2022)
The Energy and natural resources ministry (KeTSA) of Malaysia has introduced the net energy metering (NEM) 3.0, which provides an opportunity for consumers to install solar photovoltaic (PV) systems to reduce electricity bills. The NEM 3.0 introduces three new initiatives that offer 500 MW quota from 2021 till 2023. NEM has been implemented since 2016, replacing the feed-in tariff (FiT) strategy by promoting the users to utilize the generated energy in the first place before selling any surplus to the utility. As in the FiT strategy, users can only sell the generated energy at a fixed rate without utilizing it. This paper presents the comparative study between NEM and FiT for 496 kWp solar photovoltaic system in UiTM Segamat, Johor in the perspective of economy and energy practice based on the simulation result of MATLAB/Simulink software.